Medication Conformance Monitoring system (MCMS) / Johari Jalaludin - Jalaludin, Johari (Faculty of Information Technology and Quantitative Sciences, 2006)
Medication Conformance Monitoring System (MCMS) is proposed to help remind the patient for their medication and help the doctor monitors their patients in terms of medication taken. This is to make sure that the problem of noncompliance among patients can be minimized. The crucial part of the system are automatic SMS reminder function that automatically search time in database for patients that need to be reminded to take their medication and a portable monitoring pad which is Radio Frequencies Identification (RFID) tags to detect by antenna when patient pick up and put down pill containers. The data from the pad is then sent to a hospital into a central database. Therefore, the type of medications and time taken can be monitored by the physician efficiently and effectively.